Manajemen Sumber Daya Manusia Dalam Peningkatan Kompetensi Guru - Dimas Zuhri Ahmad (Jurnal Pendidikan dan Pengajaran (JUPEJA), 2024)
This research explores strategies and practices for improving teacher competence through human resource management (HR) at Nurul Ilmi Darunnajah 14 High School, Serang, Banten. The research method used is qualitative, with data collection techniques through interviews, observations, and documentation. The study's results identified four main stages in improving teacher competence through human resource management: planning, organizing, implementing, and supervising. Planning includes the development of strategies to improve the quality of education through professional development programs. Organizing involves the active participation of teachers in activities that support competency improvement such as workshops and seminars. The implementation emphasizes the mastery of learning theory and practice as well as the development of a curriculum that actively involves students. Supervision includes continuous monitoring and periodic evaluations to identify deficiencies and make improvements. With the integration of effective HR management, teacher competence can be improved, which in turn will improve the quality of education. This research provides insight for schools and related stakeholders in developing effective strategies to improve teacher competence.